Manajemen Masjid Jogokariyan Yogyakarta Sebagai Pusat Kegiatan Masyarakat - Azzam, Abdulloh; Muhyani, Muhyani (KOMUNIKA, 2019)
The mosque is the center of Islamic civilization. So, in terms of management, every mosque administrator must have competence and broad insight about management. So that the mosque functions as in the time of the Prophet Muhammad that is 70% of the use of the mosque is as a social movement and 30% is used for worship. In this study wanted to find out how the efforts made by the administrators of the Jogokariyan Mosque in managing mosque management. So that the mosque management can make the mosque as a center of community activity. This research is field research that directly participates in activities in Jogokariyan Mosque.From the results of the study, it appears that the efforts of the mosque management carried out for the mosque from time to time have had a positive impact on the community around the mosque in particular and for the outside community in general. In addition to having a positive impact, the Jogokariyan mosque has also become an inspiration for mosques throughout Indonesia in terms of its management.AbstrakMasjid merupakan pusat peradaban umat Islam. Maka dalam hal pengelolahan, setiap pengurus masjid harus memiliki kompetensi dan wawasan luas mengenai manajemen. Sehingga masjid berfungsi sebagaimana di zaman Rasulullah SAW yaitu 70% kegunaan masjid adalah sebagai gerakan sosial dan 30%nya adalah digunakan untuk ibadah. Dalam penelitian ini ingin mengetahui bagaimana usaha-usaha yang dilakukan oleh pengurus Masjid Jogokariyan dalam mengelola manajemen masjid. Sehingga pengurus masjid mampu menjadikan masjid sebagai pusat kegiatan masyarakat. Penelitian ini merupakan penelitian lapangan yang langsung turut serta akan kegiatan di Masjid Jogokariyan. Dari hasil penelitian tampak bahwa usaha para pengurus masjid yang dilakukan untuk masjid dari waktu ke waktu telah memberi dampak positif bagi masyarakat sekitar masjid pada khususnya dan bagi masyarakat luar pada umumnya. Selain memberi dampak positif, masjid Jogokariyan juga menjadi inspirasi bagi masjid-masjid seluruh Indonesia dalam hal manajemennya.